Targeting plasma cells: are we any closer to a panacea for diseases of antibody‐secreting cells?. Issue 1 (March 2016) - Low, Michael; Infantino, Simona; Grigoriadis, George; Tarlinton, David
Summary: Antibody‐secreting cells (ASCs) are critical for a functional and effective adaptive immune system. In a number of illnesses, however, these same cells contribute to the underlying disease state leading to significant morbidity and mortality. While therapeutic targeting of antibody‐secreting cells has progressed significantly over the last two decades, many of these conditions remain major health problems. In this review, we will discuss current and potential therapeutic targeting of ASCs in the context of the known biology of these cells.